An Investigation of COVID-19 Deaths in Community, Nai Mueang Sub-District, Mueang District, Chaiyaphum Province During May to June, 2021 - Sukumolanan, Pran; Kwammun, Weerapon; Klangake, Jittrawan; Thammakun, Bunpisit; Kotanu, Metinee (Journal of the office of disease prevention and control 9 Nakhon Ratchasima, 2023)
On May 16, 2021, The Office of Disease Prevention and Control 9, Nakhon Ratchasima Province received a report of the first death case from COVID-19, living in the community, Nai Mueang Sub-district, Muang district, Chaiyaphum province, and later found three more deaths on the 20, 31 May and 30 June 2021. The Office of Disease Prevention and Control 9, Nakhon Ratchasima Province, Chaiyaphum Hospital, and Muang Chaiyaphum District Health Office investigated the deaths between 16 May – 30 June 2021. The objectives were to confirm the diagnosis, find high-risk contact tracing describe epidemiological characteristics of death cases, and identify the source of the disease. Reviewing medical records, active case finding for high-risk contact cases, and environmental studies in households and communities were conducted. Family members, key persons of the community, and health care providers were interviewed, and a laboratory was applied for diagnosis. The results found that 4 COVID-19 deaths, and the case fatality rate was 4.26%. The highest and lowest age was 86 years and 62 years respectively. The average time from onset to death was 21.25 days. the average time from pneumonia to death was 19 days, and the average time from onset/finding patient to pneumonia was 2.25 days. Risk factors were older than 60 years (elderly), and having the underlying disease (100%). No one was vaccinated against COVID-19. We found that all of them (4 cases) had a history to contact with confirmed cases of COVID-19 from a community outbreak. They were infected by close family members (75%). High-risk contact was infected about 38.46%. An environmental survey was conducted and found that the community was a slum community, many households were extended family and involved in various illegal activities in the community, which induced a widespread outbreak of COVID-19. Conclusions, all of the death cases were suspected to infect close family members. All death was from risk groups; having underlying disease, the elderly, and all of them did not get vaccinated against COVID-19. Therefore, risk communication, especially among risk groups for getting vaccinated COVID-19 should be done. Moreover, protecting themselves to prevent infection from spreading to elderly people or those who have underlying diseases in the family, due to the high chance of severe illness and death.